I primi coroplasti di Alba Fucens* - Di Cesare, Riccardo; Liberatore, Daniela (O T I V M, 2024)
This paper presents some results of the excavations carried out at Alba Fucens since 2006, which have yielded new data relating to the earliest phases of the city’s life. These data were found in two stratigraphically reliable contexts: the first is located close to the forum, where a kiln that produced ceramic, votive and architectural materials for an unknown temple emerged, the second in the sanctuary of Hercules. The research offered the opportunity to investigate some aspects related to the political and religious ideology, as well as to the topographical and productive sphere of the ancient Latin colony in its earliest phase. ————————— (*) Ringraziamo gli organizzatori del Convegno per l’invito a partecipare a questa preziosa occasione di confronto. Per il costante supporto alle nostre attività di ricerca ad Alba Fucens ringraziamo la SABAP L’Aquila-Teramo, e in particolare Emanuela Ceccaroni. Autore dei paragrafi 1-2 è R. Di Cesare, dei paragrafi 3-5 è D. Liberatore. Quando non altrimenti indicato, le immagini sono degli autori.